The Orchid MADS-Box Genes Controlling Floral Morphogenesis - Wen-Chieh Tsai; Hong-Hwa Chen (The Scientific World Journal)
Orchids are known for both their floral diversity and ecological strategies. The versatility and specialization in orchid floral morphology, structure, and physiological properties have fascinated botanists for centuries. In floral studies, MADS-box genes contributing to the now famous ABCDE model of floral organ identity control have dominated conceptual thinking. The sophisticated orchid floral organization offers an opportunity to discover new variant genes and different levels of complexity to the ABCDE model. Recently, several remarkable research studies done on orchid MADS-box genes have revealed the important roles on orchid floral development. Knowledge about MADS-box genes' encoding ABCDE functions in orchids will give insights into the highly evolved floral morphogenetic networks of orchids.